2022
DOI: 10.1265/ehpm.22-00088
|View full text |Cite
|
Sign up to set email alerts
|

Association of epidural analgesia during labor with neurodevelopment of children during the first three years: the Japan Environment and Children’s Study

Abstract: Background: Epidural analgesia relives pain during labor. However, the long-term effects on neurodevelopment in children remain unclear. We explored associations between exposure to epidural analgesia during labor and childhood neurodevelopment during the first 3 years of life, in the Japan Environment and Children's Study (JECS), a large-scale birth cohort study. Methods: Pregnant women were recruited between January 2011 and March 2014, and 100,304 live births of singleton children born at full-term by vagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
5
2
Order By: Relevance
“…16 The discrepancies in findings between our study and the former study may be due to the differences in sample size, participant populations, or exposure. 16 Perinatal findings in our study indicated that CSEA does not affect the offspring immediately after birth. The labor duration was longer in the exposed group than in the control group, as observed in previous studies, 31,32 and this mechanism is explained by the lower maternal oxytocin levels with NLA administration.…”
Section: Discussioncontrasting
confidence: 81%
See 4 more Smart Citations
“…16 The discrepancies in findings between our study and the former study may be due to the differences in sample size, participant populations, or exposure. 16 Perinatal findings in our study indicated that CSEA does not affect the offspring immediately after birth. The labor duration was longer in the exposed group than in the control group, as observed in previous studies, 31,32 and this mechanism is explained by the lower maternal oxytocin levels with NLA administration.…”
Section: Discussioncontrasting
confidence: 81%
“…These results are not consistent with the findings of our study; however, our research analyzed child developmental abnormalities using the ASQ‐3, which is a screening tool for neurodevelopmental abnormalities, whereas the previous studies examined the incidence of specific conditions in children who were already diagnosed or registered, which might have accounted for the discrepancies between our findings and those of other studies. Another study using the same JECS dataset reported an increased risk of neurodevelopmental delays in communication and problem‐solving domains in children born to mothers who received EA 16 . Although maternal characteristics of the control groups between the former study and our own were similar, those of exposed groups somewhat differed 16 .…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations